2021
DOI: 10.7554/elife.65878
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila uses a tripod gait across all walking speeds, and the geometry of the tripod is important for speed control

Abstract: Changes in walking speed are characterized by changes in both the animal's gait and the mechanics of its interaction with the ground. Here we study these changes in walking Drosophila. We measured the fly's center of mass (CoM) movement with high spatial resolution and the position of its footprints. Flies predominantly employ a modified tripod gait that only changes marginally with speed. The mechanics of a tripod gait can be approximated with a simple model – angular and radial spring-loaded inverted pendulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Notably, a model with three hidden states representing tripod, tetrapod, and non-canonical gaits fit the data the best, again matching D. melanogaster (Isakov et al 2016, Pereira et al 2019, DeAngelis et al 2019) (Figure 2H). While each state displayed a characteristic distribution across behavior space (Figure 2I), tripod gait was associated with a much broader distribution in comparison to the other states, corroborating findings that tripod gait can be employed broadly across walking speeds (Chun et al 2021). These observations suggest that the biased densities in behavior space.…”
Section: A Iv)supporting
confidence: 68%
See 1 more Smart Citation
“…Notably, a model with three hidden states representing tripod, tetrapod, and non-canonical gaits fit the data the best, again matching D. melanogaster (Isakov et al 2016, Pereira et al 2019, DeAngelis et al 2019) (Figure 2H). While each state displayed a characteristic distribution across behavior space (Figure 2I), tripod gait was associated with a much broader distribution in comparison to the other states, corroborating findings that tripod gait can be employed broadly across walking speeds (Chun et al 2021). These observations suggest that the biased densities in behavior space.…”
Section: A Iv)supporting
confidence: 68%
“…Distinct gait patterns are associated with variation in kinematics over time in D. melanogaster (Mendes et al 2013, Wosnitza et al 2013, Isakov et al 2016, Pereira et al 2019, DeAngelis et al 2019, Chun et al 2021). To explore whether other species displayed similar patterns, we identified the positions of all six limbs for each species and strain and extracted the phase and swing-stance state at each frame (Figure 2F ), we found that the number of legs in stance was speed dependent across all genotypes wherein velocity decreased as the number of legs in stance increased (Figure 2G).…”
Section: A Iv)mentioning
confidence: 99%
“…Over several seconds, fluctuations in Vf may reflect changes in motor programs or behavioral goals during several strides (Fig. 1), whereas on a shorter, stride-by-stride timescale, changes in Vf reflect leg reactive forces [37][38][39] . Variability of Vf at this short timescale may reflect unexpected perturbations in the neuromechanical system within a single stride that must be corrected for in the next stride according to the motor programs and behavioral goals at play (Fig.…”
Section: A Forward Velocity-related Signal Modulates Activity In Hs Cells At Multiple Timescalesmentioning
confidence: 99%
“…Insects have long provided valuable insights into the biomechanics and neural control of locomotion (Cruse et al, 2009; Hughes, 1952; Manton, 1973; Wilson, 1966). More recently, the scalability of Drosophila behavioral measurements has allowed a variety of quantitative descriptions of the structure of walking dynamics in flies (Berman et al, 2014; Branson et al, 2009; Chun et al, 2021; DeAngelis et al, 2019; Kain et al, 2013; Katsov et al, 2017; Mendes et al, 2013; Strauss and Heisenberg, 1990). Furthermore, the majority of descending neurons (DNs) that relay movement commands from the central brain to the ventral nerve cord ( Drosophila ’s equivalent of a spinal cord) have been identified (Hsu and Bhandawat, 2016; Namiki et al, 2018).…”
Section: Introductionmentioning
confidence: 99%